2014
DOI: 10.3109/07434618.2013.878958
|View full text |Cite
|
Sign up to set email alerts
|

Tangible Symbols as an AAC Option for Individuals with Developmental Disabilities: A Systematic Review of Intervention Studies

Abstract: We reviewed nine studies evaluating the use of tangible symbols in AAC interventions for 129 individuals with developmental disabilities. Studies were summarized in terms of participants, tangible symbols used, communication functions/skills targeted for intervention, intervention procedures, evaluation designs, and main findings. Tangible symbols mainly consisted of three-dimensional whole objects or partial objects. Symbols were taught as requests for preferred objects/activities in five studies with additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
16
0
4
Order By: Relevance
“…Clearly, vision issues make decision-making and intervention in AAC more difficult, especially in the presence of language and/or intellectual disability. Available literature suggests that the introduction of AAC in the form of tangible symbols for children with both visual and motor impairments can be successful for improving comprehension, communicating effectively, and act as a stepping stone to developing more sophisticated symbol systems (Roche et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, vision issues make decision-making and intervention in AAC more difficult, especially in the presence of language and/or intellectual disability. Available literature suggests that the introduction of AAC in the form of tangible symbols for children with both visual and motor impairments can be successful for improving comprehension, communicating effectively, and act as a stepping stone to developing more sophisticated symbol systems (Roche et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research that demonstrates convincingly that augmentative and alternative communication (AAC) (i.e., the use of a wide range of unaided and aided strategies and techniques to enhance communication) can have positive effects on communication and participation, including turn taking skills, the expression of communicative functions such as requesting and commenting, acquisition of receptive and expressive vocabulary, narrative development, the length and complexity of messages expressed, acquisition of phonological awareness and literacy skills, and overall communication effectiveness (e.g., Beukelman, Fager, Ball, & Dietz, 2007;Branson & Demchak, 2009;Fried-Oken, Beukelman, & Hux, 2012;Ganz, et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Wendt, 2009). Furthermore, the research demonstrates that AAC intervention does not impede speech production or recovery; in fact, it suggests that AAC intervention can have positive effects on the frequency and intelligibility of speech production (e.g., Hanson, Beukelman, & Yorkston, 2013;Millar, Light, & Schlosser, 2006;Romski et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This research has established empirical evidence of the positive impact of AAC (Beukelman et al, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken et al, 2012;Ganz et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Walker & Snell, 2013;Wendt, 2009) and has demonstrated that these gains come at no risk to speech development or recovery (e.g., Millar, Light, & Schlosser, 2006;Romski et al, 2010). As a fi eld, we should take pride in this increased research base that has resulted in advances in evidence-based AAC services.…”
Section: Research To Advance Understanding Of Communicative Competencementioning
confidence: 99%